2014
DOI: 10.1016/j.ejvs.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen for the Treatment of Diabetic Foot Ulcers: A Systematic Review

Abstract: Current evidence shows some evidence of the effectiveness of HBOT in improving the healing of diabetic leg ulcers in patients with concomitant ischaemia. Larger trials of higher quality are needed before implementation of HBOT in routine clinical practice in patients with diabetic foot ulcers can be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(60 citation statements)
references
References 32 publications
1
57
0
2
Order By: Relevance
“…HBOT can promote healing of ischemic viable tissues via different mechanisms including oxygenation as long as there is no necrosis 36,37. The non-viable, necrotic tissue cannot be oxygenated even with HBOT and therefore it is being surgically removed.…”
Section: Discussionmentioning
confidence: 99%
“…HBOT can promote healing of ischemic viable tissues via different mechanisms including oxygenation as long as there is no necrosis 36,37. The non-viable, necrotic tissue cannot be oxygenated even with HBOT and therefore it is being surgically removed.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment has been shown to improve tissue hypoxia, vessel perfusion, reduce inflammation and edema, and increase angiogenesis [ 106 ]. Numerous studies in patients with DFUs have shown that patients undergoing HBOT show increased healing rates and reduced risk of a major limb amputation [ 107 , 108 ]. Unfortunately, HBOT is cost-prohibitive to the average patient, and while it has an over 20-year track record in the clinic, is still not a complete answer for treating non-healing diabetic foot wounds.…”
Section: Current Therapies To Ameliorate Diabetic Wound Healingmentioning
confidence: 99%
“…The increase of oxygen levels in the hypoxic wound is essential for the cells involved in the healing process (neutrophils, fibroblasts, macrophages) to carry out their specific repair functions [ 6 ]. Linked to this observation, HBOT has been evidenced to diminish the number of major lower limb amputations among diabetic people [ 7 , 8 ]. The increased oxygen availability during HBOT is an essential mediating factor associated to wound collagen deposition, cross-linking and neovascularization [ 9 ].…”
Section: Introductionmentioning
confidence: 99%